A nutritional and socio-economic study of Philippi farm children and their mothers during November 1986 - Whittaker, Stuart (Department of Public Health and Family Medicine, 2018)
A community based survey to determine the nutritional status using anthropometric methods, of children and mothers and to assess certain socio-economic factors was carried out during November and December 1986 in Philippi, a predominantly vegetable farming area. Twenty-one (43%) of the 49 vegetable farms which were included in the study were selected by stratified random sampling. All children in the 0-6 year age group and their parents on the selected farms were included in the sample which consisted of 129 children and 212 parents. Questionnaires were administered and subjects' weights and heights were measured. It was found that 47% of children were below the National Centre for Health Statistics 5th percentile weight for age and 58% were under the 5th percentile height for age. There were 47 child deaths out of 279 births over a six-year period, thirty-four of which had occurred in the first year of life. Twenty eight percent of children had a birth weight of less than 2.5 kg. The number of cases of tuberculosis (10%) and severe diarrhoea (31%) contracted within the first year of life is unacceptably high. Twenty four percent of mothers were malnourished in terms of body mass index and fifty five percent of mothers were illiterate. Fifty nine percent of mothers were regular farm workers who worked for an average of 10.2 hours per day and a wage of R0.44 per hour. Grossly inadequate facilities existed for the care of children while the mothers worked. The average amount spent on food was insufficient to maintain normal nutrition. Although 91.5% of mothers breast fed their children and fed for a mean duration of 13.4 months, breast feeding was not exclusive. Supplementary feeding was introduced on average at 3 months of age. The long working hours of working mothers made it difficult for them to breast feed their children satisfactorily. Acceptance of the family planning services was high and immunisation cover was good. These statistics reflect the effects of extreme poverty and neglect of a community which is totally reliant on its employers for its livelihood. The parents poor educational level, coupled with their meagre financial and other physical resources gives them and their children little opportunity to improve their station in life and leaves them open to the scrounge of malnutrition and disease. Similarly, the dearth of educational and other child care facilities will ensure that this disastrous trend continues. A multidisciplinary approach, including active community involvement of both farmers and workers, to the many physical and social problems is urgently needed if the unacceptable human suffering is to be stopped.